Conversation with Enrique Iturriaga - Estenssoro Fuchs, Juan Carlos (2018)
This interview was conducted in Lima, at Enrique Iturriaga's home, in July 2009. It is a conversation that sought to recall different moments of his life, with special emphasis on his musical activity, reviewing his most important compositions. A small part of this material, edited by me and then revised and adapted together with Enrique, was published by the magazine Caretas in a special issue of Fiestas Patrias where readers were offered a CD with the Junín and Ayacucho Symphony, conducted by Miguel Harth-Bedoya. On the occasion of the celebrations for the centenary, I am now presenting a much broader selection of this material.